Juvenile justice system in Nepal. (Kathmandu School of Law (KSL), 2003)
Various programs under the project of the Institut for menneskerettigheder, Denmark conducted by Kathmandu School of Law for the Center for Legal Research and Resource Development, CeLRRd; includes briefly proceedings of a conference also.